Speech and language therapy students' perception of learning through the incorporation of clinical simulation workshops: a mixed-methods study - María Magdalena Muñoz-Montes; Ignacio Villagrán-Gutiérrez; Francisca Pozo-Tapia; Paulina Tapia-Tapia; Yolanda Castro-Soares; Eduardo Fuentes-López (Revista CEFAC, 2021)
ABSTRACT Purpose: this study had two aims: (1) Analyse students' perceptions of achieved learning in the simulation workshops implemented in multiple areas in a Speech and Language Therapy curricula, and (2) Establish the effect of incorporating simulation workshops in the students' comprehensive evaluation of the course. Methods: a survey on perceived learning was validated, including quantitative and qualitative sections, and applied to students that participated in the simulation workshops (n=241). Additionally, quantitative information from a survey of systematic application on the comprehensive perception of the courses that implemented workshops was analysed (n=277). Results: the quantitative section showed a positive perception of learning through the simulation workshop and coincided with the qualitative section's positive opinions. Additionally, the courses that implemented simulation workshops showed a positive evaluation in methodology, feedback, and organization. Conclusion: the students had a positive perception of the incorporation of clinical simulation workshops. The survey's sections provided complementary information regarding learning through clinical simulation.